2007
DOI: 10.1080/08276331.2007.10593408
|View full text |Cite
|
Sign up to set email alerts
|

The Emotional Intelligence of Entrepreneurs

Abstract: Entrepreneurship research has recognized the entrepreneur as catalyst to the new venture process. A popular stream of research not yet applied to entrepreneurship has been the study of the emotional intelligence of entrepreneurial venture leaders. This web-based exploratory study collected self-assessment data of emotional competencies on successful young entrepreneurs. Participating entrepreneurs reported that they demonstrated high levels of self-confidence, trustworthiness, achievement orientation, service … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
1
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 67 publications
4
52
1
3
Order By: Relevance
“…Females have been found to generally lower selfefficacy and entrepreneurial career intentions Crant (1996) entrepreneurs provides the impetus to high willpower that drives their passions, innovativeness and social interactions. This sanctions their choice and ability to integrate social, environmental and economic aspects in the enhancement of value (Goss, 2005(Goss, , 2008Kurucz et al, 2008;Rhee and White, 2007).…”
Section: Overview Of the Field Of Entrepreneurshipmentioning
confidence: 98%
See 1 more Smart Citation
“…Females have been found to generally lower selfefficacy and entrepreneurial career intentions Crant (1996) entrepreneurs provides the impetus to high willpower that drives their passions, innovativeness and social interactions. This sanctions their choice and ability to integrate social, environmental and economic aspects in the enhancement of value (Goss, 2005(Goss, , 2008Kurucz et al, 2008;Rhee and White, 2007).…”
Section: Overview Of the Field Of Entrepreneurshipmentioning
confidence: 98%
“…Social entrepreneurs pursue a variety of social causes requiring high levels of willpower, innovativeness, social interaction and sanctioning (Goss, 2005(Goss, , 2008Rhee and White, 2007). This study adopts the stand that personality traits play an important role in moulding the individual's perceptions and behaviours which are instrumental in driving the social mission and legitimacy of the enterprise.…”
Section: The Influence Of Personality Traits and Demographic Factorsmentioning
confidence: 99%
“…Such managers use emotional intelligence to communicate with others in better ways to enable and support creativity (Zhou and George, 2003). In addition, Rhee and White (2007) found that entrepreneurs try to decrease the feelings of risk taking in pursuing opportunities by utilizing their emotional intelligence. Recent work by Home (2011) has also focused on the extent to which values and attitudes (aspects of emotional intelligence)…”
Section: Emotional Intelligence and Entrepreneurial Stylementioning
confidence: 99%
“…Some studies that apply EmoI to the area of entrepreneurship research (Cross & Travaglione, 2003;Rhee & White, 2007); Zampetakis, Gotsi, Andriopoulos & Moustakis, 2009) and, more specifically, with entrepreneurial intent (Zampetakis et al, 2009) have been developed.…”
Section: Emotional Intelligencementioning
confidence: 99%